Chipotle Mexican Grill : food with integrity? - Walker, Russell, 1972-; Merkley, Greg (London : Kellogg School of Management, 2017)
By any measure, Chipotle Mexican Grill was a success story in the restaurant business. It grew from one location in 1993 to over 2,000 locations by 2016 and essentially created the fast casual dining category. Its stock appreciated more than 1,000% in the ten years following its 2006 IPO.However, after more than 20 years without a major reported food safety incident, Chipotle was revealed as the source of multiple outbreaks of illness from norovirus, salmonella, and E. coli that sickened nearly 600 people in 13 states in 2015. The company closed stores, spent several months under investigation by the U.S. Centers for Disease Control and Prevention (CDC) and other health organizations, and faced a criminal investigation in connection with the incidents.After a much-publicized closing of all of its stores on February 8, 2016, and numerous changes to its food sourcing and preparation practices, Chipotle tried to win back customers with dramatically increased advertising and free food promotions.However, on April 26, the chain announced its first-ever quarterly loss as a public company. Same-store sales for the first quarter were 29.7% lower than in the previous year. Operating margins fell from 27.5% to 6.8% over the same period, and the company's share price was down 41% from its summer 2015 high.
Originally published in Walker, R., & Merkley, G. (2017). Chipotle Mexican Grill: Food with integrity? 5-316-501. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Chipotle Mexican Grill, Inc; Restaurant management; Food poisoning -- United States